A Novel Technology for Measurements of Dielectric Properties of Extremely Small Volumes of Liquids - Wei-Na Liu (International Journal of Antennas and Propagation)
A high sensitivity sensor for measurement radio frequency (RF) dielectric permittivity of liquids is described. Interference is used and parasitic effects are cancellation, which makes the sensor can catch weak signals caused by liquids with extremely small volumes. In addition, we present the relationship between transmission coefficient and permittivity of liquids under test (LUT). Using this sensor, quantitative measurements of the dielectric properties at 5.8 GHz are demonstrated of LUTs. Experiments show that the proposed method only requires the volume of 160 nanoliters for liquids. Therefore, the technology can be used for RF spectroscopic analysis of biological samples and extremely precious liquids.